Adaptive NOMA towards 5G green wireless network. Issue 3 (10th February 2020) - Jain, Preksha; Gupta, Akhil
Abstract: A nonorthogonal multiple access (NOMA) enabled downlink single‐cell communication network with cooperating relay nodes, is considered in this article. NOMA simultaneously transmits signals to a group of users. The formation of the group users, in NOMA, depends on their spatial restrictions. These spatial restrictions are defined by the transmission range of the relay equipment. Therefore, it is important to find the transmission range of the relay. This article presents a novel angle selection scheme for finding the transmission range of the relay. Ever‐increasing cellular traffic needs improvement in data rates and power saving. So, an adaptive NOMA scheme in which the system adaptively chooses its working model is proposed in this article. The adaptive NOMA scheme maximizes the sum rate and optimizes the energy efficiency of the fifth‐generation communication network. It also reduces the power consumption at the circuit of the end‐user equipment, hence, achieving power saving. Comprehensive numerical results emphasize that the proposed scheme achieves higher system energy efficient as compared to the conventional NOMA scheme. Such an adaptive framework also improves the average signal‐to‐interference noise ratio and the fairness factor, as shall be examined. The implications of proposing an adaptive NOMA network are evaluated through simulation results. Abstract : This paper presents an Angle Selection Scheme for finding the transmission range of the relay. Ever‐increasing cellular traffic needs improvement in data rates and power saving. So, an adaptive NOMA scheme in which the system adaptively chooses its working model is proposed in this paper. The adaptive NOMA scheme maximizes the sum rate and optimizes the energy‐efficiency of the 5G communication network. It also reduces the power consumption at the circuit of the end‐user equipment, hence, achieving power saving.